Sub-family relationships of Bradinothrips Hood and Parascolothrips Mound (Thysanoptera, Thripidae) - Zhang, Shimeng; Mound, Laurence A.; Feng, Jinian (Zootaxa, 2019)
A cladistic analysis based on 31 morphological characters of female adults recovered two genera currently placed in subfamily Thripinae, Bradinothrips Hood and Parascolothrips Mound, as closely related to two Panchaetothripinae genera, Monilothrips Moulton and Zaniothrips Bhatti. Thus, following the results of this analysis, we propose the transference of the first two genera to subfamily Panchaetothripinae, under the tribe Monilothripini.